2015
DOI: 10.1016/j.ajpath.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements for IL-17A and IL-22 in Cecal versus Colonic Inflammation Induced by Helicobacter hepaticus

Abstract: Type 17 helper T-cell cytokines have been implicated in the pathogenesis of inflammatory bowel disease, a chronic condition affecting the gastrointestinal tract, but information regarding their contribution to pathology in different regions of the gut is lacking. By using a murine model of bacteria-induced typhlocolitis, we investigated the role of IL-17A, IL-17F, and IL-22 in cecal versus colonic inflammation. Cecal, but not colonic, pathology in C57BL/6 mice inoculated with Helicobacter hepaticus plus antieI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…whereas, anti-Il-17 treatment increased severity of cecal pathology but not colonic pathology (Kullberg et al, 2006;Morrison et al, 2015). Thus, it is possible that the progression of preneoplastic dysplasia to cancer promoted by HhCDT requires a host factor(s) and a defined microflora only present in the ceca and ileocecocoloic junction.…”
Section: Stat3 Can Be Activated By Diverse Agents Including Growth Famentioning
confidence: 83%
See 1 more Smart Citation
“…whereas, anti-Il-17 treatment increased severity of cecal pathology but not colonic pathology (Kullberg et al, 2006;Morrison et al, 2015). Thus, it is possible that the progression of preneoplastic dysplasia to cancer promoted by HhCDT requires a host factor(s) and a defined microflora only present in the ceca and ileocecocoloic junction.…”
Section: Stat3 Can Be Activated By Diverse Agents Including Growth Famentioning
confidence: 83%
“…Consistent with these previous findings, in the Hh‐infected mice, there was more severe pathology in the ceca and ileocecocolic junction compared with transverse and distal colon at both time points and in the HhCDT mutant‐infected mice at 10 WPI. In addition, previous studies in anti‐Il10R‐treated C57BL/6 mice reported that Il‐22 and Ifnγ are required for inducing colonic inflammation but not for cecal inflammation by H. hepaticus ; whereas, anti‐Il‐17 treatment increased severity of cecal pathology but not colonic pathology (Kullberg et al, ; Morrison et al, ). Thus, it is possible that the progression of preneoplastic dysplasia to cancer promoted by HhCDT requires a host factor(s) and a defined microflora only present in the ceca and ileocecocoloic junction.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, there were no differences in the cecum typhlocolitis index scores between genders, but the female mice had significantly higher pathological scores in the colon at both 6 and 10 weeks p.i. The underlying differences in the expression of cytokine receptors in different anatomical locations of the intestine may contribute to this difference (39). At 6 weeks p.i, multifocal hepatitis was noticed in the infected mice which may indicate H.japonicum infection in the liver by translocating the intestinal barrier into hepatic tissues or alternatively, indirect effect of systemic cytokine response due to the primary intestinal infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…H. hepaticus‐ or H. typhlonius ‐infected mice are frequently used as a model for a better understanding of the pathogenesis of inflammatory bowel diseases in humans. IL‐23 produced by monocytes, IL‐17 and IL‐22 produced by Th17 cells, IFNγ and IL‐17 produced by Th1/17 cells, and TNFα produced by colitogenic T cells seem to be associated with the development of intestinal inflammation. Ray et al .…”
Section: Pathogenesis Of Infections With Nhphmentioning
confidence: 99%